Hippocampal NMDA receptors and anxiety: at the interface between cognition and emotion. - Barkus, C; McHugh, S; Sprengel, R; Seeburg, P; Rawlins, J; Bannerman, D (2010)
David De Wied had a fundamental interest in the brain and behaviour, with a particular interest in the interface between cognition and emotion, and how impairments at this interface could underlie human psychopathology. The NMDA subtype of glutamate receptor is an important mediator of synaptic plasticity and plays a central role in the neurobiological mechanisms of emotionality, as well as learning and memory. NMDA receptor antagonists affect various aspects of emotionality including fear, anxiety and depression, as well as impairing certain forms of learning and memory. The hippocampus is a key brain structure, implicated in both cognition and emotion. Lesion studies in animals have suggested that dorsal and ventral sub-regions of the hippocampus are differentially involved in dissociable aspects of hippocampus-dependent behaviour. Cytotoxic lesions of the dorsal hippocampus (septal pole) in rodents impair spatial learning but have no effect on anxiety, whereas ventral hippocampal lesions reduce anxiety but are without effect on spatial memory. This role for the ventral hippocampus in anxiety is distinct from the role of the amygdala in other aspects of emotional processing, such as fear conditioning. Recent studies with genetically modified mice have shown that NR1 NMDA receptor subunit deletion, specifically from the granule cells of the dentate gyrus, not only impairs short-term spatial memory but also reduces anxiety. This suggests that NMDA receptors in ventral hippocampus may be a key locus supporting the anxiolytic effects of NMDA receptor antagonists. These data support Gray's neuropsychological account of hippocampal function.